PENGARUH POLA PENGERINGAN TERHADAP RENDEMEN DAN KUALITAS MINYAK ATSIRI DAUN PUCUK MERAH (Syzygium oleana.) - Suryanto Suryanto; Rudianda Sulaeman; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Essential oil is one of forest product instead of wood have benefit and is one of product of non migas and important for Indonesian. Pucuk merah (Syzygium oleana) on of enough plant potential for to know oil characteristics of essential oil. This research have purpose to know of the yild and quality essential oil for pucuk merah plant with steam method in some pattern drying leaves. The time of research was do in October until November 2016 in Laboratory Forestry and Laboratory Technique the Earth Water and Mineral University Riau. This experience using Completely Random Design consisting of 3 treatments and 3 replication. The yild essential oil obtained later and observed the color, scent and solubility in ethanol. Drying patterns can increase the  amount of the yild essential oil. The treatment by drying the leaves at temperatures 35 °C during 12 hours have the yild average highest (0,38%) of result. Quality of essential oil pucuk merah plant as follows : Scent of essential oil have a scent typical most were in has been tested by organoleptic test is pucuk merah leaves shoot with leaves drying at temperatures 35 °C during 12 hours most 90% panelis declare scent typical. The color of essential oil who has been visually observed from the 3 treatment resulted in the same color is yellow. Essential oil of pucuk merah have a sollability of ethanol in accordance SNI clove oil in the ratio 1 : 2 is the essential oil produced from fresh leaves.Keywords: The Yild, Essential Oil, Pucuk Merah, Drying